2018
DOI: 10.1590/0001-3765201720170206
|View full text |Cite
|
Sign up to set email alerts
|

Climatic characteristics of the 2010-2016 drought in the semiarid Northeast Brazil region

Abstract: This study discusses the climatological aspects of the most severe drought ever recorded in the semiarid region Northeast Brazil. Droughts are recurrent in the region and while El Nino has driven some of these events others are more dependent on the tropical North Atlantic sea surface temperature fields. The drought affecting this region during the last 5 years shows an intensity and impact not seen in several decades in the regional economy and society. The analysis of this event using drought indicators as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
224
0
66

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 374 publications
(338 citation statements)
references
References 36 publications
13
224
0
66
Order By: Relevance
“…Visual analysis shows the major severe droughts that impacted the region, namely, 1982–1983, 1992–1993, 1997–1998, 2007–2008, and 2012–2016 (gray‐shaded areas of the right panel of Figure ). Among those events, the large drought of 2012–2016, considered to be the largest drought, both in magnitude and duration, of the last three decades (Getirana, ; Brito et al, ; Marengo et al, , ). The right panel of Figure shows the time evolution of the peak values of relative frequency over the period of analysis, indicating a significant trend toward intensification in magnitude and duration of droughts along the period 1982–2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual analysis shows the major severe droughts that impacted the region, namely, 1982–1983, 1992–1993, 1997–1998, 2007–2008, and 2012–2016 (gray‐shaded areas of the right panel of Figure ). Among those events, the large drought of 2012–2016, considered to be the largest drought, both in magnitude and duration, of the last three decades (Getirana, ; Brito et al, ; Marengo et al, , ). The right panel of Figure shows the time evolution of the peak values of relative frequency over the period of analysis, indicating a significant trend toward intensification in magnitude and duration of droughts along the period 1982–2016.…”
Section: Resultsmentioning
confidence: 99%
“…Since climate variability in NEB is related to sea surface temperature (SST) variations, both in the Pacific and Atlantic oceans (Kayano and Capistrano, 2014;Rodrigues and Mcphaden, 2014;Marengo et al, 2017aMarengo et al, , 2017b, we compared the recent trends observed in drought maps against the time evolution of tropical SST indices.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, there was a strong "El Niño" effect across the Amazon region [46], which contributed to reduced precipitation and increased temperatures. In the study region, the 2015 annual average temperature was 27.5 • C, 0.9 degrees warmer than the climatological norm based on 30 years of data [47]. The maximum and minimum absolute temperatures were also found to be higher in 2015, and the dry period (precipitation < 100 mm) extended for 6 months (July to December), compared to the usual 3-month period (September to November).…”
Section: Regeneration Dynamics Of Mora Paraensismentioning
confidence: 62%
“…This drought event has been studied by many authors. The year 2012 was identified as the most severe for the period, followed by the biennial 2015-2017 [7,31,36,42]. Brito et al [43] highlighted the intensity of the droughts during the period of 1981 to 2016, including its severity, frequency, and duration, and considering hydrometeorological and agricultural aspects.…”
Section: Discussionmentioning
confidence: 99%